Trypanosoma cruzi: Multiple nucleoside diphosphate kinase isoforms in a single cell - Miranda, Mariana Reneé (2008)
Nucleoside diphosphate kinases (NDPKs) are multifunctional enzymes involved mainly in the conservation of nucleotides and deoxynucleotides at intracellular levels. Here we report the characterization of two NDPKs from the protozoan parasite Trypanosoma cruzi, the etiological agent of Chagas disease. TcNDPK1 and TcNDPK2 were biochemically characterized presenting different kinetic parameters and regulation mechanisms. NDPK activity was mainly detected in soluble fractions according to the digitonin extraction technique; however 20% of the activity remains insoluble at digitonin concentrations up to 5mgml(-1). TcNDPK1 is a short enzyme isoform, whereas TcNDPK2 is a long one containing a DM10 motif. In addition, two other putative NDPK genes (TcNPDK3 and TcNDPK4) were detected by data mining at the T. cruzi genome database. The large number and diversity of NDPK isoforms are in agreement with those previously observed for other T. cruzi phosphotransferases, such as adenylate kinases.